A new adaptive second‐order sliding mode controller design for nonlinear systems with multiple uncertainties. (27th November 2022) - Ding, Chen; Ma, Li; Ding, Shihong
Summary: This study is dedicated to solving the problem of a new adaptive second‐order sliding mode (SOSM) controller design for a type of nonlinear systems with multiple uncertainties by using adding a power integrator (API) and the parameter separation techniques. Supported by the finite‐time Lyapunov theory, the finite‐time stability of the closed‐loop system under the proposed adaptive SOSM controller has been firmly guaranteed. The significant advantages here lie in that the prior knowledge about the bounds of uncertainties is not required in the designed adaptive SOSM control approach, and the switching gain can be tuned dynamically. Finally, a numerical example is presented to indicate the notable feature and effectiveness of the designed adaptive SOSM approach.